Education in Architecture: Transitions towards Sustainable Development - Castellanos Tuirán, Alexandra Isabel (Corporación Universitaria del Caribe, CECAR., 2020)
Three aspects related to Education in Architecture are analyzed in order to find common ground and convergences: the social development of Western culture, from the environmental point of view; the evolution of Education in the West, since the appearance of the first modern theories; and the evolutionary process of Architecture training from a historical and epistemological perspective. It reflects on the relationship of these issues, from a critical view of the teaching of Architecture, a discipline in which many times it must be thought that these aspects travel along divergent paths.